Identification of a low tiller gene from a new plant type cultivar in rice (Oryza sativa L.) - Uddin, Md. Nashir (Breed Sci, 2016)
We characterized a rice introgression line, YTH34, harboring a chromosome segment from a New Plant Type (NPT) cultivar, IR65600-87-2-2-3, in the genetic background of an Indica Group elite rice cultivar, IR 64, under upland and irrigated lowland conditions in Japan. The number of panicles (as an indicator of tiller number) and number of spikelets per panicle of YTH34 were lower than those of IR 64 under irrigated lowland conditions, but both of those as well as culm length, panicle length, seed fertility, panicle weight, whole plant weight, and harvest index were dramatically reduced under upland conditions. And the low tiller of YTH34 was confirmed to start after the maximum tiller stage. In particular, the decrease of panicle number was remarkable in upland, so we tried to identify the chromosome location of the relevant gene. Through segregation and linkage analyses using F(3) family lines derived from a cross between IR 64 and YTH34, and SSR markers, we found that low tiller number was controlled by a single recessive gene, ltn2, and mapped with the distance of 2.1 cM from SSR marker RM21950, in an introgressed segment on chromosome 7. YTH34 harboring ltn2 and the genetic information for DNA markers linked will be useful for genetic modification of plant architectures of Indica Group rice cultivar.